The meat of the matter: a rule of thumb for scavenging dogs?. Issue 4 (1st October 2016) - Bhadra, Anandarup; Bhattacharjee, D.; Paul, M.; Singh, A.; Gade, P.R.; Shrestha, P.; Bhadra, Anindita
Abstract : Animals that scavenge in and around human settlements need to utilise a broad range of resources, and thus generalist scavengers are likely to be better adapted to human-dominated habitats. In India, free-ranging dogs ( Canis lupus familiaris ) live in close proximity with humans in diverse habitats, from forest fringes to metropolises, and are heavily dependent on humans for their food. It has been argued that the ability to digest carbohydrates was one of the driving forces for dog domestication. Though dogs are better adapted to digest carbohydrates than other canids, pet dogs show a clear preference for animal proteins. Our observations on streets of urban and semi-urban localities show that the free-ranging dogs are scavengers which primarily receive carbohydrate-rich food from humans. Their source for animal protein is typically garbage bins and leftovers, and such resources are rare. Using a series of field-based experiments, we test if the free-ranging dogs have adapted to a generalist scavenging lifestyle by losing preference for animal protein. Our experiments show that the free-ranging dogs, which are descendants of the decidedly carnivorous gray wolf ( Canis lupus lupus ), have retained a clear preference for meat, which is manifested by their choice of anything that smells of meat, irrespective of the actual nutrient content. The plasticity in their diet probably fosters efficient scavenging in a competitive environment, while a rule of thumb for preferentially acquiring specific nutrients enables them to sequester proteins from the carbohydrate-dominated environment.